Conjugated Conductive Polymer Materials and its Applications: A Mini-Review - Lu, Huizhi; Li, Xunlai; Lei, Qingquan (Frontiers in Chemistry, 2021)
Since their discovery 50 years ago, conjugated conducting polymers have received increasing attention owing to their unique conductive properties and potential applications in energy storage, sensors, coatings, and electronic devices such as organic field-effect transistors, photovoltaic cells, and light-emitting devices. Recently, these materials have played a key role in providing a more comfortable environment for humans. Consequently, the development of novel, high-performance conjugated conductive materials is crucial. In this mini-review, the progress of conjugated conductive materials in various applications and the relationship between the chemical structures and their performances is reviewed. This can aid in the molecular design and development of novel high-performance conjugated polymer materials.